Human Filariasis in Travelers and Migrants: A Retrospective 25-year Analysis at the Institute of Tropical Medicine, Antwerp, Belgium. (31st August 2021) - Bottieau, Emmanuel; Huits, Ralph; Van Den Broucke, Steven; Maniewski, Ula; Declercq, Steven; Brosius, Isabel; Theunissen, Caroline; Feyens, Anne-Marie; Van Esbroeck, Marjan; van Griensven, Johan; Clerinx, Jan; Soentjens, Patrick
Abstract: Background: Information on human filariasis in international travelers is scarce. We describe the epidemiology, clinical presentation, and outcome of these infections in a reference travel clinic over the past decades. Methods: We reviewed all cases of filariasis diagnosed at the Institute of Tropical Medicine, Antwerp, Belgium, from 1994 to 2018. Diagnosis was obtained by either parasitological methods (confirmed) or strict clinical case definitions (probable). We assessed the characteristics of cases at diagnosis and response to therapy within 3–12 months. Results: A total of 320 patients (median age: 41 years; 71% males) were diagnosed with 327 filarial infections ( Wuchereria bancrofti = 6, Onchocerca volvulus = 33, Loa loa = 150, Mansonella perstans = 130, unspecified species = 8). Diagnosis was confirmed in 213/320 (67%) patients. European long-term travelers accounted for 166 patients (52%) and visitors/migrants from tropical countries for another 110 (34%). Central Africa was the likely region of acquisition for 294 (92%) patients. The number of filariasis cases decreased from 21.5/year on average in the 1990s to 6.3/year in the past decade, when loiasis became predominant. Cases reported symptoms in >80% of all filarial infections but mansonellosis (45/123 single infections; 37%). Lymphatic filariasis and onchocerciasis cases responded well to conventional therapy. However, 30% of patients with loiasis and mansonellosis experienced treatment failure (with diethylcarbamazine and levamisole-mebendazole, respectively). Conclusions: The burden and species distribution of filariasis in travelers evolved in the past decades. Most presentations were symptomatic. Case management would benefit from more effective therapies for loiasis and mansonellosis. Abstract : In a 25-year retrospective analysis conducted in a European reference travel clinic, the caseload of filariasis decreased in international travelers and the species distribution evolved. Morbidity was substantial. Effectiveness of conventional therapy was not optimal in loiasis and mansonellosis cases.